Wild beauty - McLemore, Anna-Marie (Feiwel and Friends, an imprint of Macmillan Publishing Group, LLC, 2017)
For nearly a century the Nomeolvides women have tended the grounds and lush estate gardens of La Pradera. They have a tragic legacy: if they fall in love too deeply, their lovers vanish. When a strange boy appears in the gardens, he is a mystery to Estrella and to her family, but he's even more a mystery to himself. He knows nothing more about who he is or where he came from than his first name. As Estrella tries to help Fel piece together his unknown past, they uncover secrets as dangerous as they are magical.